Partnerships for Empowerment : Participatory Research for Community-Based Natural Resource Management - Wilmsen, Carl, 1956-; Elmendorf, William; Fisher, Larry; Ross, Jacquelyn; Sarathy, Brinda; Wells, Gail (Earthscan, 2008)
'This text presents models of research sorely needed in the literature and for work in communities.' Kathleen Martin assistant professor of ethnic studies California Polytechnic State University 'Moving beyond a presentation of orthodoxy and idealized goals of participatory research this book provides honest and critical accounts of efforts in the US to apply participatory research to natural resource management. The case studies and synthesis chapters provide invaluable lessons to aid better understanding of the complexities and challenges involved in this very important approach to research.